Association between multimorbidity and falls and fear of falling among older adults in eastern China: a cross-sectional study - You, Liuqing; Guo, Lihua; Li, Na; Zhong, Jieming; Er, Yuliang; Zhao, Ming (Frontiers in Public Health, 2023)
Abstract Background: Growing evidence has reported an association between multimorbidity and falls and fear of falling (FOF) in the elderly, however, the results regarding this association from China are limited. Our study aimed to investigate the association between multimorbidity and falls and FOF in the elderly in eastern China. Methods: We conducted a cross-sectional study in Zhejiang Province, Eastern China, which recruited a provincial representative sample of adults aged ≥ 60 years. A structured questionnaire including demographic characteristics, chronic diseases, history of falls in the past 12 months, and FOF, was administered by all participants. The exposure variable was multimorbidity, which was defined as the presence of two or more chronic diseases and medical conditions in the same individual. The outcomes included a history of falls and FOF. Multivariate logistic regression was used to evaluate the association between multimorbidity and falls and FOF in the elderly. Results: In total of 7774 participants were included in the analysis, among whom 3898 (50.1%) were female, with a mean ± standard deviation age is 72.9±8.4 years. Multimorbidity was associated with the increased risk of falling in the elderly (adjusted odds ratio [OR], 1.99; 95% confidence interval [CI]:1.55-2.36). The ORs for having experienced single fall and repeated falls were 1.85 (95% CI: 1.42–2.42) and 3.45 (95% CI: 1.47–6.97), respectively, with multimorbidity compared with those without chronic diseases. The elderly with multimorbidity were more likely to report FOF compared with the elderly without chronic diseases (adjusted OR, 1.49; 95%CI:1.30-1.70). Moreover, the association between multimorbidity and FOF remained significant in the elderly with a history of fall (OR, 1.57; 95%CI:1.04-2.38). Conclusions: The association between multimorbidity and falls and FOF is significant in the Chinese population and the effects of multimorbidity on falls and FOF do not vary according to the frequency and history of falls in the elderly.